A Synopsis of Begonia (Begoniaceae) from Southeastern Sulawesi including four new species. Phytotaxa 381 (1): 27–50. - Ardi, Wisnu H.; Chikmawati, Tatik; Witono, Joko R.; Thomas, Daniel C. (Phytotaxa, 2019)
N/A